GnRH agonist pretreatment for frozen embryo transfer among women with polycystic ovary syndrome: a narrow systematic review and meta-analysis of randomized controlled trials - Yiqing Wu; Mixue Tu; Yifeng Liu; Dan Zhang (BMC, 2024)
Abstract Background Frozen embryo transfer (FET) is usually recommended for women with polycystic ovary syndrome (PCOS) undergoing In vitro fertilization (IVF). While there is no consensus as to the optimal protocol of endometrial preparation for FET. The effect of gonadotropin-releasing hormone agonist (GnRH-a) pretreatment for FET among women with PCOS remains controversial. Purpose We intend to explore whether GnRH-a pretreatment could improve clinical outcomes for women with PCOS undergoing FET. Methods PubMed, Embase, ClinicalTrials.gov, Cochrane Library, and Web of Science were searched up to May 16, 2024. Eligible studies involved patients with PCOS undergoing FET and receiving GnRH-a pretreatment for endometrial preparation, with artificial cycle (AC) as the control therapy. Only randomized controlled trials (RCTs) published in Chinese and English were included. Data extraction was performed independently by two authors. Effect was quantified using odd ratios (ORs) with 95% confidence intervals (CIs) using random-effect models with the Mantel-Hansel (M-H) method in Revman software. Quality of outcomes was evaluated using the GRADEpro system. Primary outcomes contained the clinical pregnancy rate, miscarriage rate, and live birth rate. Secondary outcomes included the incidence of preterm labor and gestational diabetes mellitus (GDM). Results Ninety-seven records were initially retrieved, with 21 duplicates and 65 articles excluded after title and abstract screening. Seven studies were excluded due to retrospective design, leaving three RCTs with 709 participants. Among them, 353 received GnRH-a pretreatment as the intervention group and 356 received AC as the control group. No significant differences were observed in the clinical pregnancy rate (OR 1.09, 95% CI 0.75 to 1.56, P = 0.66), miscarriage rate (OR 0.73, 95% CI 0.28 to 1.90, P = 0.52), live birth rate (OR 0.87, 95% CI 0.61 to 1.25, P = 0.46), and the risk of preterm labor (OR 1.45, 95% CI 0.79 to 2.65, P = 0.23) and GDM (OR 0.73, 95% CI 0.37 to 1.48, P = 0.39) between the two groups. Conclusions In this meta-analysis, GnRH-a pretreatment does not confer any advantages and appears unnecessary for women with PCOS undergoing FET. Additional RCTs should focus on maternal complications and the health of offspring.